Muscle focal vibration in healthy subjects: evaluation of the effects on upper limb motor performance measured using a robotic device - Aprile, Irene; Di Sipio, Enrica; Germanotta, Marco; Simbolotti, Chiara; Padua, Luca (European journal of applied physiology, 2016)
Purpose Muscle vibration is a technique that applies a low-amplitude/high-frequency vibratory stimulus to a specific muscle using a mechanical device. The aim of this study was to evaluate, using robot-based outcomes, the effects of focal muscle vibration, at different frequencies, on the motor performance of the upper limb in healthy subjects. Methods Forty-eight volunteer healthy subjects (age: 31 ± 8 years) were enrolled. Subjects were assigned to three different groups: the first group, in which subjects underwent muscle vibration treatment with a frequency of 100 Hz; the second group of subjects underwent the same treatment protocol, but using a frequency of vibration of 200 Hz; finally, the control group did not undergo any treatment. The robot-based evaluation session consisted of visually guided reaching task, performed in the sagittal plane. Results Our results showed that the vibration treatment improved upper limb motor performance of healthy subjects from the baseline (T0) to 10 days after the end of the treatment (T2), but only the group treated with a frequency of 200 Hz reached statistical significance. Specifically, in this group we found an increase of the number of repetitions (T0: 51.4 ± 22.7; T2: 66.3 ± 11.8), and the smoothness of the movement, as showed by a decrease of the Normalized Jerk (T0: 10.5 ± 2.8; T2: 7.7 ± 0.5). Conclusion The results of our study support the use of focal muscle vibration protocols in healthy subjects, to improve motor performance.